Micromechanical performance of high-density polyethylene: Experimental and modeling approaches for HDPE and its alumina-nanocomposites. (January 2021) - Balobanov, Viacheslav; Verho, Tuukka; Heino, Vuokko; Ronkainen, Helena; Pelto, Jani
Abstract: The scratch resistance of polymers is important for numerous applications, as scratching can lead to degradation of surface properties and also represents an elementary process in abrasive wear. However, scratching of polymers is a complex process involving several modes of deformation, and theoretical understanding of it is incomplete. Numerical modeling is a potentially useful means towards a clearer picture of the scratching process, but the central role of tip-substrate contact and highly localized large deformations makes finite element analysis (FEA) challenging. Here, we take further the numerical approach by investigating a highly ductile semi-crystalline polymer by FEA and taking the inherent rate dependency of polymers into account by using an elasto-viscoplastic material model. Two γ-Al2 O3 and f-Al2 O3 HDPE nanocomposites, which have shown themselves to be suitable for tribological applications, are studied. We discussed the effect of nanofillers on the scratch behavior and highlight the significance of recovery properties, which still pose a challenge to numerical modeling. Highlights: The scratching behavior of neat HDPE and its alumina nanocomposites is studied experimentally. A recent elasto-viscoplastic material model is used for modeling neat HDPE in finite-element simulations. A detailed description of finite element models and solution to problems arising in simulations are addressed. Pros and cons of the considered material model are revealed by comparing the experimental and numerical results, and the next steps to improve the material model and its use for modeling polymer nanocomposites are discussed. The effect of alumina nanofillers on the scratching behaviour of HDPE is discussed.